2021
DOI: 10.3389/fsufs.2021.714596
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Short-Term Fertilizer Potential of Mealworm Frass Using a Pot Experiment

Abstract: The forecasted growth of insect production in the next few years will generate high quantities of frass (insect excreta). Although frass is increasingly considered a potential fertilizer, the dynamics of nutrient supply by frass is still poorly understood. Here, we aimed at gaining insight into the short-term fertilizer value of frass from mealworm (Tenebrio molitor L.) in order to optimize its sustainable use in agroecosystems. Using a short-term pot experiment, we showed that, even though frass has a great p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
3
23
0
1
Order By: Relevance
“…For example, previous studies have reported higher yields and nutritional quality of maize, tomatoes, kales, French beans, cow peas, chilli pepper, shallots and barley grown using H. illucens frass fertilizer and meal worm frass fertilizer compared to conventional fertilizers 27 , 28 , 42 , 52 , 53 . Furthermore, soil amendment with frass fertilizer from H. illucens and T. molitor was found to suppress soil borne pathogens, stimulate soil microbial activity, reduce soil acidity and salinity, improve nitrogen mineralization, and increase availability of nutrients in the soil 29 31 , 33 , 53 , thus improving the soil quality for plant growth. It is therefore anticipated that adoption of insect fertilizer would contribute to improving food security by in SSA reversing the worrying trends in soil degradation, nutrient mining and declining crop productivity 1 , 8 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have reported higher yields and nutritional quality of maize, tomatoes, kales, French beans, cow peas, chilli pepper, shallots and barley grown using H. illucens frass fertilizer and meal worm frass fertilizer compared to conventional fertilizers 27 , 28 , 42 , 52 , 53 . Furthermore, soil amendment with frass fertilizer from H. illucens and T. molitor was found to suppress soil borne pathogens, stimulate soil microbial activity, reduce soil acidity and salinity, improve nitrogen mineralization, and increase availability of nutrients in the soil 29 31 , 33 , 53 , thus improving the soil quality for plant growth. It is therefore anticipated that adoption of insect fertilizer would contribute to improving food security by in SSA reversing the worrying trends in soil degradation, nutrient mining and declining crop productivity 1 , 8 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that reported significant effects of mealworm frass on ryegrass (Lolium multiflorum Lam.) and barley (Hordeum vulgare L.) shoot biomass applied frass at a rate equivalent to 250-500 kg N ha −1 , which is much higher than the N required by the plants (Houben et al, 2020(Houben et al, , 2021. A previous study also applied a high rate of frass (1:1 or 2:1 soil-to-frass ratio) and found significant effects on the growth of lettuce (Lactuca sativa var.…”
Section: Plant Biomass and Nutrient Uptakementioning
confidence: 99%
“…To properly utilize the frass in a sustainable way, their effect on soil health and plant growth should be evaluated. The very limited studies available to date have shown that the application of frass increases yield (Rosmiati et al, 2017;Houben et al, 2020Houben et al, , 2021, activates plant defense responses against abiotic (Poveda, 2021) and biotic stress (Quilliam et al, 2020), and improves soil microbial activities (Gebremikael et al, 2020). On the contrary, few other studies found negative effects of BSF frass and other commercially available frass on soil quality and plant growth, such as phytotoxicity (Alattar et al, 2016;Watson et al, 2021a,b) and excessive nitrite accumulation in soil (Watson et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Some pot tests have shown the potential of entomocompost, obtained from substrates of various kinds, to reduce mineral fertilization in several crops, as for instance: With mealworm (Tenebrio molitor L.) frass, in barley [25] and ryegrass [41], and with BSF frass, in basil and Sudan grass [42], chinese cabbage [43], yardlong bean [44], lettuce [45,46], ryegrass [45,47], maize [48] and swiss chard [49].…”
Section: Data In the Context Of The Trinomial "Soil X Plant X Fertilizer"mentioning
confidence: 99%
“…In any case, the medium-and long-term promotion and resilience of the fertility of the soils, which should be fostered by insect frass, would be translated, as for the generality of organic fertilizers, by the improvement of the structure of the soils and its capacity to retain water and crop nutrients and as well as by symbiotic interaction with the soil microbial flora and with the plant. Many knowledge within this perspective is still needed, but also a lot have been accumulated, allowing for hopeful evidences, such as: better use efficiency of P and K [57]; improved soil fertility and defense against pathogens [58]; suppression against Pythium ultimum [59]; influence on soil N availability [60]; stimulation of soil microbial activity and diversity [25]; not impairing hygienic properties of soils [47]; improvement of microbial activity [41]; increased dehydrogenase activity [61]; or increased enzyme activity (dehydrogenase and β-glucosidase) [46]. These data augur well, but medium and long-term field trials are indispensable for continued soil fertility management, since organic matter resilience is not its greatest virtue, particularly in tropical and sub-tropical climates.…”
Section: Data In the Context Of The Trinomial "Soil X Plant X Fertilizer"mentioning
confidence: 99%